Answer:
that x is represented by 3 as the value
Step-by-step explanation:
Answer:
x = -3, y =3
Step-by-step explanation:
y = -4/3x - 1
y = 1/3x + 4 -------> 4y = 4/3x + 16
Adding the first equation and the new second equation together:
5y = 15 ------> y = 3
Plug y = 3 into one of the original equations:
3 = 1/3x + 4
-1 = 1/3x
x = -3
Answer:
y=3x+10
Step-by-step explanation:
First, put the equation into point-slope form.
y-y1=m(x-x1)
y-4=3(x+2)
Next, distribute 3 to (x+2) and simplify.
y-4=3x+6
y=3x+10
Answer:
B is your answer,
With the factors of ( 2 )( 1 ), the lay out of the equation makes only sense with answer B.

(an improper fraction) can be simplified to

(a mixed number)